Notes from the Anthesis of a Super Ville: Influence of Digital Paradigm on Istanbul’s Architectural Context - Görgülü, Tülin; í–kem, Selim; Erdönmez, Ebru (ARCC Conference Repository, 2019)
Word superville is used to indicate the integration of a city with the market, servicing utilities and media on a global scale through digital technology. Another term that is associated with the same meaning is information city (or global city). However the term superville addresses a dual structure of connotations which on one side refers to urban relations in global scale and on the other to a body of urban formations smaller than a town (the villes) that come together to form a more complex unity. Trying to integrate itself into the global financial and informational network, the term superville denotes a bit from both associations in Istanbul’s case.